Hepatitis B Virus positive (HBsAg positive) among the blood donors attended at transfusion medicine department, Dhaka Medical College Hospital, Bangladesh: a one year study (Journal of Dhaka Medical College, 2015)
Context: The possibility of hepatitis transmission through blood and blood products is very high and pretransfusion screening is mandatory by law in our country. The present study was carried out to find out the prevalence of Hepatitis B virus positive (HBsAg positive) among the blood donors attended the Department of Transfusion Medicine, Dhaka Medical College Hospital, Dhaka, in 2012. Method: This cross sectional study was carried out in the Department of Transfusion Medicine, Dhaka Medical College Hospital, Dhaka, between January and December 2012. Total blood donors were 27,560. Blood donors of 18-60 years of both sexes were included in this study. Results: Among 27,560 blood donors, relative blood donors were 21,081 (76.49%) and voluntary blood donors were 6,479 (23.50%). Among total blood donors male and female were 23,776 (86.26%) and 3784 (13.73%) respectively. 25,906 (93.99%) were in 18-40 years age group and 1,654 (6%) were in 41-60 years age group. A total of 453 were detected as HBsAg seropostive. Among them, relatives of the patients were 363 (1.7%) and voluntary donors were 90 (1.4%). DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21528 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 163-166